Efficient Irrigation Technologies for Corn—A Comparison - F. R. Lamm; D. M O'Brien (Kansas Agricultural Experiment Station Research Reports, 2022)
This study was conducted from 2016–2021 at the Kansas State University Northwest Research-Extension Center near Colby, KS. Two irrigation systems, subsurface drip irrigation (SDI) and mobile drip irrigation (MDI) were compared for two irrigation capacities equivalent to 0.25 in./day and 0.167 in./day. Irrigation amounts were similar for the two systems when comparing the equivalent capacities, averaging 13.3 and 11.4 inches per acre. When averaged over the six-year period, SDI and MDI corn grain yields were 242.5 and 239.2 bu/a, respectively. Although irrigation amounts for the two systems at an equivalent irrigation capacity were similar, total crop water use was less for SDI than for MDI. There was greater soil water depletion with MDI than with SDI. Crop water productivity was greater with SDI than with MDI. Both of these advanced irrigation systems are acceptable for corn production in the Central Great Plains.
Keywords: Irrigation; Irrigation efficiency; Irrigation technologies; Subsurface drip irrigation; mobile drip irrigation